Rodzina i miłość w epoce Ja. Wyzwania dla pedagogiki - Ściupider-Młodkowska, Mirosława (Studia Edukacyjne, 2019)
The theoretical part of this article draws on terminology defined by theorists such as J. C. Kauffman, N. Luhmannn, Ch. Lasch, E. Beck-Gernsheim, U. Beck, A. Giddens, L. Jamienson, E. Illouz, and Z. Bauman. The research on partnership relations in the narcissistic culture are published in the book by the article author: Ściupider-Młodkowska M., Love in the time of Me. A socio-pedagogical study, Poznań 2018. The fight for an approval and innovatory ideas for a happy partnership life (which has been observed in my research on biographies of relationships) does not entirely come from “free” choices. Therefore, we may conclude that to some extent the culture of narcissism has an impact on a quality of relationships and relations between people in general. In the wider context, the article tries to provide an answer to the question of transgression of common responsibility for a success or a failure in relations between people. Interpersonal contacts are increasingly controlled or created by the market as well as the world of technicization. As a result, their character is changed into shortterm relations where only an Ego of individuals is promoted and general narcissism culture is spread. Pedagogues are concerned about building identity of young people mostly in social media according to the phrase Selfie ergo sum. Pedagogy cannot ignore the influence of media on the social development of teenagers (which includes their sexual development, too). To prevent the acquisition of negative patterns, an educational program needs to be proposed which will teach a critical approach to social media and help build sustained interpersonal relations.